Cognitive effects of GABAergic antiepileptic drugs - Czubak, Anna; Nowakowska, Elzbieta; Burda, Kinga; Kus, Krzysztof; Metelska, Jana (Arzneimittelforschung, 2010)
Many patients undergoing long-term treatment of epilepsy complain of memory disorders, which entail worse quality of life. The risk factors generating memory disorders include: morphological brain damage, the duration and course of epileptic seizures (conscience disorders), the time of diagnosis (the risk is greater if epileptic seizures start early in life), drug resistance, the presence of interseizure changes in the EEG in the form of sharp-wave discharges or sharp spike-wave/slow spike-wave complexes and improper pharmacotherapy (exceeding the admissible concentration of drugs in blood serum, polytherapy).GABAergic neurotransmission of older antiepileptic drugs (barbiturates, benzodiazepines) makes them particularly prone to produce modest, but statistically significant disruption of cognitive processes. This explains the search for new antiepileptic drugs that will improve, or at least not impair, cognitive functions. The improvement of cognitive functions by new generation antiepileptic drugs results, among others, from their non-GA-BAergic mechanisms: they influence the ion channels and glutaminergic transmission.
Keywords: Antiepileptic drugs; Cognitive effects; GABA